Efeitos do ácido gálico na sinalização purinérgica em linfócitos e plaquetas de ratos submetidos a um modelo experimental de diabetes - Pereira, Aline da Silva (2017)
Diabetes mellitus (DM) is a chronic metabolic disease associated with hyperglycemia, systemic inflammatory changes and vascular endothelial dysfunction. NTPDase, 5'-nucleotidase and adenosine deaminase (ADA) are important enzymes involved in the regulation of inflammatory, immune and platelet responses and thus may are the suitable therapeutic targets in DM. Gallic acid has many biological properties such as antihyperglycemic, antioxidant, anti-inflammatory and antiaggregant actions. Thus, the objective of this study was to evaluate the effect of gallic acid on hematological parameters and on the ectonucleotidases activities in platelets, lymphocytes and serum of diabetic rats. Male Wistar rats were divided into four groups: I - control, II - gallic acid, III - diabetic and IV - diabetic / gallic acid. DM was induced in the animals by injection of streptozotocin (65 mg / kg i.p.). Gallic acid was administered orally seven days after induction of DM, at a dose of 30 mg/kg during to time of 21 days. The results demonstrated that administration of gallic acid was not able to revert to hyperglycemia in diabetic rats. In relation to the hematological parameters, the mean corpuscular hemoglobin concentration was decreased while the red blood cell distribution was increased in the diabetic group, and gallic acid was able to reverse these alterations. Gallic acid also reversed the diabetes-induced increase in NTPDase activity in lymphocytes and platelets and ADA activity in lymphocytes. On the other hand, in animals of group IV was observed a in the activity of the ADA in the platelets. A decrease in ATP hydrolysis and an increase in ADP and AMP hydrolysis in diabetic rats were observed in serum and gallic acid treatment was capable to revert only changes in ATP hydrolysis. Our results suggest that gallic acid has beneficial effects on immune and thromboregulatory responses in DM, and that these effects may be related to the modulation of purinergic signaling in lymphocytes, platelets and serum.